Implementation of the Apostle Paul's teaching based on Romans 12:6 – 8 to the Christian teachers - Nugroho, Widhi Arief; Daliman, Muner; Suparti, Hana; Susilo, D. (Technium Social Sciences Journal, 2021)
In Romans 12:6 -8 the Apostle Paul’s teaching to the Christian teachers to give the totality of life. Because by giving this totality of life, he can be an inspiration and a strategic figure radiating the Real picture of Christ for his students. But the reality in the field is that there are still Christian teachers who have not shown the totality of their lives for God. There are Christian teachers who are often late, and even less serious in carrying out their teaching duties. This indicates that the teacher has not implemented the Apostle Paul's teaching based on Romans 12:6-8. The first advice of the Apostle Paul in Romans 12:1-2 emphasizes that Christians must offer their lives as true worship, namely by offering his work as a living body offering by being a professional teacher like Christ, but from the results of surveys and interviews, it is known that there are still Christian teachers who still teach less seriously just to seek fulfillment of 24 hours face-to-face as a minimum teacher hour requirement. This indicates that the teacher has not implemented to Paul's teaching based on Romans 12:6-8